Mozambican gas: an economically viable solution to the South African electricity crisis? - Brown, Stuart (My University, 2016)
The recent significant discoveries of gas in Mozambique could provide a much needed solution to the South African electricity crisis, but at what cost? This research report seeks to determine the economic viability of utilising Mozambican Gas to produce electricity by using data from the Integrated Resource Plan 2010-2030 Update of 2013 in a levelised cost of electricity model. The Mozambican gas fields are yet to be developed and the final price at which gas will be available is unclear, but a price range determined by ICF international in a study for the World Bank is assumed for the purposes of the study, with the results yielding a range levelised cost of energy. The results of the levelised cost determine that Mozambican gas can be utilised to provide an economical solution to the south African electricity crisis, but the price at which gas is available will determine the type of generation, either peaking power, midmerit and or baseload generation.
Submitted to School of Chemical and Metallurgical Engineering, Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, South Africa 24 August 2016
Keywords: Power resources; Renewable energy sources; Natural gas reserves--Economic aspects--Mozambique; Natural gas reserves--Economic aspects--South Africa; Gas industry--Mozambique; Gas industry--South Africa